Literatur Review Manfaat Makanan Mengandung Probiotik Bagi Kesehatan - Olivia Salma Ramadhani; Luluk Chotimah; Shafa' Luthfiana Widya Susanti; Rohmad Nur Huda; Rohmat Nur Salim; Liss Dyah Dewi Arini (Lembaga Pengembangan Kinerja Dosen, 2024)
This article discusses a literature review on the benefits of probiotic-containing foods for health. Fermented foods are food products processed with the help of microorganisms or enzymes, producing components beneficial to human health. In Indonesia, fermented foods such as tempeh, tapai, green tea, pickled vegetables, and bekasam are known for their high health value and potential to gain international recognition. This literature study aims to analyze the benefits of probiotics in fermented foods, particularly regarding digestive health, immunity, and disease prevention. Probiotics such as Lactobacillus plantarum, Lactobacillus curvatus, and Lactobacillus GG, as well as indigenous yeasts like Saccharomyces cerevisiae and Candida tropicalis, play a crucial role in the fermentation of traditional Indonesian foods. These microorganisms help improve gut microbiota balance, inhibit the growth of pathogenic microbes, and produce beneficial bioactive compounds. Research indicates that probiotics can enhance immune responses, reduce inflammation, and improve glucose metabolism and lipid profiles. The findings of this study underscore the importance of fermented foods as a public health strategy, considering their contributions to supporting digestive function, strengthening immunity, and preventing various diseases. Traditional Indonesian fermented foods not only hold cultural value but also have significant potential as functional foods to improve quality of life.